If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 60 + 2x = 12x + 50 Reorder the terms: 60 + 2x = 50 + 12x Solving 60 + 2x = 50 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 60 + 2x + -12x = 50 + 12x + -12x Combine like terms: 2x + -12x = -10x 60 + -10x = 50 + 12x + -12x Combine like terms: 12x + -12x = 0 60 + -10x = 50 + 0 60 + -10x = 50 Add '-60' to each side of the equation. 60 + -60 + -10x = 50 + -60 Combine like terms: 60 + -60 = 0 0 + -10x = 50 + -60 -10x = 50 + -60 Combine like terms: 50 + -60 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| 7+13x=6x+42 | | 8+10x=2x+32 | | 4x+13=12+9x | | 54+15x=72+6x | | 5x+63=12x+35 | | 10x+14=3x+42 | | 5x+90=15x+40 | | 6x+32=24+10x | | 36+14x=63+5x | | 12+10x=18+7x | | 6x+24=9x+6 | | 36+14x=72+5x | | 12+8x=4x+36 | | 8x+42=14x+36 | | 6x+28=16+10x | | 8+7x=10+5x | | 5x+42=12x+14 | | 3x+7+2(3+x)= | | 4x+10=2+6x | | 24+7x=12+10x | | 2x+30=10+7 | | 42+4x=10x+24 | | 3x+7+3(3+x)= | | 20+15x=70+5x | | 66+12x=1x+88 | | 6x+64=14x+48 | | 7x+40=10+12x | | (5/6x)-2x=(5/3)-(8/3) | | 33+14x=55+3x | | 8+3x=4+7x | | 32+13x=5x+48 | | 66+2x=13x+55 |